Performance evaluation of ultrasonic assisted wire electrical discharge turning for TI-6AL-4V material - Mohd Zakaria, Muhammad Akmal (2023)
Recently, the machining of precise cylindrical forms on hard and difficult-to-cut materials by spark erosion has gained popularity. However, the performance of this process always reflects the drawbacks in terms of distortion in gap equilibrium due to sensitivity of rotating workpieces in which the surface finish of the machined parts and the material removal rate (MRR) are not satisfying even when advanced computing and statistical optimisation methods have been used to obtain the best machining conditions. Solving the conflict of MRR and surface roughness is challenging because no single combination of parameters can provide the best machining performance. Therefore, the main objective of this research is to evaluate the performance of ultrasonic assisted in wire electrical discharge turning (WEDT) for Ti-6Al-4V on MRR and surface roughness. The ultrasonic attachment accessories are fabricated and retrofitted into the existing WEDT. The collected data for parametric study is analysed by analysis of variance (ANOVA). For the evaluation of surface roughness, five machining paths are evaluated on the basis of conventional turning operations, such as straight-turning and cone angle. The machined surface conditions are characterised by elemental analysis and surface morphology in post-evaluation measurement. Results showed that, the integration of ultrasonic vibration to WEDT revealed positive effects, where the average of MRR and surface roughness are improved by 2.9% and 13.4%, respectively, even though the proposed ultrasonic parameters have not been optimised yet. The electrode wire debris generated during machining, which can resolidify to the machined surface, is able to be reduced with the integration of ultrasonic vibration to WEDT machining when using low ultrasonic amplitude (10 μm). After performing with multi-objective parameter optimization with the goal of maximising the MRR and minimising the surface roughness using genetic algorithm method, there is a 5.2% improvement for the MRR and 11.6%–27.9% improvement for surface roughness compared to conventional WEDT. In conclusion, this study successfully applied the ultrasonic vibration to rotating workpieces, proved the capability in machining and enhanced both MRR and surface roughness.